Efecto agudo del láser de baja potencia en la fatiga del bíceps braquial de atletas de voleibol - Froio, Juliana Lôbo [UNESP]; Renno, Ana Claudia Muniz; Chagas, Eduardo Federighi Baisi; de Campos, Felipe Guilherme Leite [UNESP]; Pucci, Renata Lumena Altruda [UNESP]; Kishi, Marcos Seizo; Pedroni, Cristiane Rodrigues [UNESP] (FapUNIFESP (SciELO), 2017)
Introduction: Low-power laser therapy has among its aims to aid the recovery of biological tissues, attenuating the effects of muscle fatigue and contributing to the improvement of performance in athletes. Methodological aspects still limit the conclusions of the acute effect of laser therapy on muscular performance. Objective: To verify the acute effect of low-power therapeutic laser in the induced fatigue in biceps brachii of volleyball athletes. Methods: This was a randomized double-blind study, approved by Institutional Review Board of UNESP, Marília. Nineteen volleyball athletes of both sexes participated in this study. Electromyographic data were collected from the biceps brachii muscle in isometric exercise of the elbow flexion before and after the application of the therapeutic laser. A dumbbell with 75% of the force peak, obtained by a load cell, was used for the fatigue protocol. The volunteers then underwent laser (active or placebo) application on six points of the biceps brachii muscle. The EMG data were analyzed in the frequency domain using the Myosystem® software. The distribution of normality was verified by the Shapiro-Wilk test, and repeated measures ANOVA (split plot) was used to test the interaction between time and group. Results: No significant interaction between group and time was observed for any analyzes variables, indicating that the irradiated group did not show advantages over the placebo group. Conclusion: After the proposed fatigue protocol, a single low-power laser application was not sufficient to produce positive effects on strength performance and on the electromyographic signal of the biceps brachii muscle of volleyball athletes.
Efeito agudo do laser de baixa potência na fadiga do bíceps braquial de atletas de voleibol
Acute effect of low-power laser in fatigue of biceps brachii of volleyball athletes
Keywords: Electromyography; Muscle fatigue; Phototherapy; Volleyball